Genetic aberrations leading to MAPK pathway activation mediate oncogene-induced senescence in sporadic pilocytic astrocytomas - Jacob, Karine; Quang-Khuong, Dongh-Anh; Jones, David T. W.; Witt, Hendrik; Lambert, Sally; Albrecht, Steffen; Witt, Olaf; Vezina, Catherine; Shirinian, Margret; Faury, Damien; Garami, Miklos; Hauser, Peter; et al. (Clinical cancer research, 2011)
Purpose: Oncogenic BRAF/Ras or NF1 loss can potentially trigger oncogene-induced senescence (OIS) through activation of the mitogen-activated protein kinase (MAPK) pathway. Somatic genetic abnormalities affecting this pathway occur in the majority of pilocytic astrocytomas (PA), the most prevalent brain neoplasm in children. We investigated whether OIS is induced in PA.Experimental Design: We tested expression of established senescence markers in three independent cohorts of sporadic PA. We also assessed for OIS in vitro, using forced expression of wild-type and V600E-mutant BRAF in two astrocytic cell lines: human telomerase reverse transcriptase (hTERT)-immortalized astrocytes and fetal astrocytes.Results: Our results indicate that PAs are senescent as evidenced by marked senescence-associated acidic β-galactosidase activity, low KI-67 index, and induction of p16INK4a but not p53 in the majority of 52 PA samples (46 of 52; 88.5%). Overexpression of a number of senescence-associated genes [CDKN2A (p16), CDKN1A (p21), CEBPB, GADD45A, and IGFBP7] was shown at the mRNA level in two independent PA tumor series. In vitro, sustained activation of wild-type or mutant BRAF induced OIS in both astrocytic cell lines. Loss of p16INK4a in immortalized astrocytes abrogated OIS, indicative of the role of this pathway in mediating this phenomenon in astrocytes. OIS is a mechanism of tumor suppression that restricts the progression of benign tumors. We show that it is triggered in PAs through p16INK4a pathway induction following aberrant MAPK activation.Conclusions: OIS may account for the slow growth pattern in PA, the lack of progression to higher-grade astrocytomas, and the high overall survival of affected patients.